A combined search for the standard model Higgs boson at root S=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2008)
We present new results of the search for WH --> lvb (b) over bar production in p (p) over bar collisions at a center-of-mass energy of root S = 1.96 TeV, based on a dataset with integrated luminosity of 0.44 fb(-1). We combine these new results with previously published searches by the do collaboration, for WH and ZH production analyzed in the E(T)b (b) over bar final state, for ZH (--> l(+)l(-)b (b) over bar) production, for WH (-->. WWW) production, and for H (--> W W) direct production. No signal-like excess is observed either in the W H analysis or in the combination of all D0 Higgs boson analyses. We set 95% C.L. (expected) upper limits on sigma(p (p) over bar --> WH) x B(H --> b (b) over bar) ranging from 1.6 (2.2) ph to 1.9 (3.3) pb for Higgs boson masses between 105 and 145 GeV, to be compared to the theoretical prediction of 0.13 pb for a Standard Model (SM) Higgs boson with mass in m(H) = 115 GeV. After combination with the other do Higgs boson searches, we obtain for in H = 115 GeV an observed (expected) limit 8.5 (12.1) times higher than the SM predicted Higgs boson production cross section. For m(H) = 160 GeV, the corresponding observed (expected) ratio is 10.2 (9.0). (C) 2008 Elsevier B.V. All rights reserved.